The Subsequent Market Value of Former REO Properties. (22nd January 2016) - Rutherford, Jessica; Rutherford, Ronald C.; Strom, Elizabeth; Wedge, Lei
Abstract : In this study, we find the subsequent price for a property initially sold as a real estate owned (REO) property occurs at market prices. The subsequent price to the REO purchaser is related to indicators that the property has been remodeled, renovated, or updated. This suggests that the difference between the price received by servicers/lenders that foreclose and sell a REO property, and the price received by subsequent property owners that sell is in large part due to timely improvements made postforeclosure. Lenders are not selling REO properties at irrational prices, but rather at prices that reflect the condition of the properties.